Pengaruh Microteaching Terhadap Kesiapan Mengajar Pengenalan Lapangan Persekolahan (PLP) Mahasiswa Prodi Pendidikan Administrasi Perkantoran - Ainul Mukholidah; Durinta Puspasari (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to determine the effect of microteaching readiness on teaching readiness for school field introduction (PLP) for students of office administration education study program, Faculty of Economics and Business, Surabaya State University. This research is a correlational study using a quantitative approach. The samples in this study were all office administration education study programs class of 2019, totaling 54 people. Data collection techniques using interviews, questionnaires and documentation. The data analysis method used in this study is simple linear regression analysis. The results showed that the microteaching variable had an effect on the readiness to teach school field introduction (PLP) variable which was obtained from the t-value of 11,473 > t-table of 1,675 and a sig value of 0,000 <0,05. Keywords : Microteaching, Readiness to Teach, Introduction to Schooling Field (PLP).